CXCR4 promotes tumor stemness maintenance and CDK4/6 inhibitors resistance in ER-positive breast cancer - Qiangfeng Shi; Wang Yang; Yiye Ouyang; Yujie Liu; Zijie Cai (Breast Cancer Research)
Abstract Background CDK4/6 inhibitors have significantly improved the survival of patients with HR-positive/HER2-negative breast cancer, becoming a first-line treatment option. However, the development of resistance to these inhibitors is inevitable. To address this challenge, novel strategies are required to overcome resistance, necessitating a deeper understanding of its mechanisms. Recent research has identified several dysregulated genes in CDK4/6 inhibitors-resistant breast cancer, but the underlying mechanism is complex due to tumor heterogeneity and warrants further investigation. Methods RNA sequencing and KEGG pathway analysis was carried out to identify the mainly dysregulated genes in CDK4/6 inhibitors-resistant breast cancer cells. The effects of CXCR4 knockdown and overexpression via siRNAs and plasmids transfection were examined by mammosphere formation, RT-qPCR, flow cytometry, MTT and colony formation assays. The regulation mechanisms were analyzed by RT-qPCR, western blotting and immunofluorescence experiments. Mouse xenografts were used to analyze the role of CXCR4 in regulation palbociclib sensitivity in vivo. Additionally, we collected the clinical samples and performed immunohistochemistry to analyze the clinical significance of CXCR4. Results In our study, we focused on cancer stem cells, a critical contributor to cancer metastasis and therapy resistance, and detected an upregulation of stemness in our established palbociclib-resistant ER-positive breast cancer cells. Additionally, our research pinpointed CXCR4 as a pivotal gene responsible for maintaining cancer stemness and promoting palbociclib resistance. Mechanistically, CXCR4 activates the WNT5A/β-catenin signaling pathway by enhancing the expression of WNT5A and β-catenin, facilitating the nuclear translocation of β-catenin protein. Targeting CXCR4 using siRNAs or small molecular inhibitors effectively reduces cancer stemness and reverses palbociclib resistance both in vitro and in vivo. Clinical sample analysis further underscores the overactivation of the CXCR4/WNT5A/β-catenin axis in palbociclib-resistant breast cancer, suggesting CXCR4 as a potential biomarker for predicting resistance to CDK4/6 inhibitors. Conclusions Collectively, our study demonstrates that CXCR4 overexpression plays a vital role in maintaining breast cancer stemness and promoting resistance to CDK4/6 inhibitors through the activation of the WNT5A/β-catenin pathway. Targeting CXCR4 may offer a promising therapeutic approach for advanced CDK4/6 inhibitor-resistant ER-positive breast cancer.